Comparison of hematopoietic stem cell transplantation and repeated intensified immunosuppressive therapy as second-line treatment for relapsed/refractory severe aplastic anemia - Zhang, Lining; Li, Jianping; Liang, Weiru; Zhang, Xiaoyu; Chen, Shulian; Shi, Yuanyuan; Hao, Mengze; Zhao, Xiaoli; Gong, Ming; Wei, Jialin; He, Yi; Jiang, Erlie; et al. (Frontiers in Immunology, 2024)
The optimal treatment for patients with severe aplastic anemia (SAA) who fail an initial course of antithymocyte globulin (ATG) plus cyclosporine has not yet been established. We compared the effectiveness of allogeneic hematopoietic stem cell transplantation (allo-HSCT) (n = 36) with repeated immunosuppressive therapy (IST) (n = 33) for relapsed/refractory SAA between 2007 and 2022. In the IST group, patients were retreated with ATG (n = 16) or high-dose cyclophosphamide (n = 17). The overall response rate was 57.6% at 6 months and 60.6% at 12 months. In the allo-HSCT group, patients received a transplant from a matched sibling donor (n = 6), matched unrelated donor (n = 7) or haploidentical donor (n = 23). All patients achieved neutrophil engraftment, and there were no cases of primary graft failure. The cumulative incidences (CI) of grade II-IV, III-IV acute graft-versus-host disease (GVHD) was 36.1% ± 0.7%, 13.9% ± 0.3% at day +100. The 4-year CI of chronic GVHD (cGVHD) was 36.2% ± 0.7%, with moderate to severe cGVHD at 14.9% ± 0.4%. Compared with IST, HSCT recipients showed much higher hematologic recovery rate at 3-, 6-and 12-months (63.9%, 83.3% and 86.1%, respectively, p < 0.001). The estimated 4-year overall survival (OS) (79.8% ± 6.8% vs. 80.0% ± 7.3%, p = 0.957) were similar; however, the failure-free survival (FFS) was significantly better in the HSCT group (79.8% ± 6.8% vs. 56.6% ± 8.8%, p = 0.049). Of note, children in the HSCT cohort were all alive without treatment failures, exhibiting superior OS (100% vs. 50.0% ± 17.7%, p = 0.004) and FFS (100% vs. 50.0% ± 17.7%, p = 0.004) than children in the IST cohort. Subgroup analysis revealed that younger patients (age ≤ 35 years), especially children, and those with refractory SAA benefited more from HSCT. Therefore, for these patients, salvage HSCT may be more preferable than a second course of IST.